Mass Cytometry Imaging for the Study of Human Diseases—Applications and Data Analysis Strategies - Baharlou, Heeva; Canete, Nicolas P.; Cunningham, Anthony L.; Harman, Andrew N.; Patrick, Ellis (Frontiers in Immunology, 2019)
High parameter imaging is an important tool in the life sciences for both discovery and healthcare applications. Imaging Mass Cytometry (IMC) and Multiplexed Ion Beam Imaging (MIBI) are two relatively recent technologies which enable patient clinical samples to be simultaneously analysed for up to 40 parameters at subcellular resolution. Importantly, due to their ease of use, these ‘Mass Cytometry Imaging’ (MCI) modalities are being rapidly adopted for studies of the immune system in both health and disease. In this review we discuss, first, the various applications of MCI to date. Second, due to the inherent challenge of analysing high parameter spatial data, we discuss the various approaches that have been employed for the processing and analysis of data from MCI experiments.